An unusual cause of spontaneous pneumothorax. (3rd May 2011) - Spyratos, Dionisios; Kalpakidis, Vasilios; Giouleka, Paschalina; Chloros, Diamantis; Sichletidis, Lazaros
Abstract : Bronchopulmonary sequestration is a congenital pulmonary malformation consisting of a non-functioning region of lung parenchyma that receives systemic arterial blood supply. The authors present the case of a 31-year-old male who presented with spontaneous pneumothorax as the initial clinical manifestation of an intralobar bronchopulmonary sequestration. There was a persistent air leak through the chest tube which remained in the pleural cavity for 12 days. CT revealed an area of increased opacity, with focal calcifications and a small eccentric cavity in the posterior basal region of the left lower lobe. Aortography established the final diagnosis.